A Consideration for Increasing Post-Release Financial Success - Mielitz, Katherine (Kate) S. (American journal of criminal justice, 2020)
There is an ever-growign body of research indicating the importance and effectivenss of correctional programming. The main goal of release is autonomy, which inclues financial independence. This can be achieved not only through employment, but also having the financial capability to budget, pay bills, and properly handle one's finances. It is important to understand the perceptions of financial literacy and its relationship with release in order to create effective programming. This study fills a gap in the literature that explores predictive factors regarding the attitudes and perceptions of inmates regarding their financial matters and choices. Aspects of incarceration (e.g. length of time incarcerated, number of times incarcerated, and type of crime) were found to be associated with financial attitudes, anticipated post-release social support, and perceptions of control over financial behavior for transitional center residents within six months of release.